Synchrotron X-ray Radiography as a Highly Precise and Accurate Method for Measuring the Spatial Distribution of Liquid Water in Operating Polymer Electrolyte Membrane Fuel Cells. Issue 2 (1st January 2017) - Chevalier, S.; Ge, N.; George, M. G.; Lee, J.; Banerjee, R.; Liu, H.; Shrestha, P.; Muirhead, D.; Hinebaugh, J.; Tabuchi, Y.; Kotaka, T.; Bazylak, A.
Abstract : For the first time, the precision and the accuracy of liquid water content measurements in operating polymer electrolyte membrane (PEM) fuel cells from synchrotron X-ray radiographic imaging are determined. We define the precision of X-ray radiographic-based water measurements by combining two types of uncertainties. In the uncertainty of type A, the standard deviation of the average through-plane water thickness distribution is determined as a function of time and space. In the uncertainty of type B, the effects of the instrumentation (camera readout noise and X-ray energy level) in the Beer-Lambert law are considered. The volume of liquid water in the gas diffusion layer (GDL) is quantified with the greatest precision (plus or minus 5%) when using a beam energy of 24 keV and a low camera readout noise. The accuracy of our synchrotron X-ray-based liquid water measurements is determined from the direct comparison to neutron radiography measurements reported by Kotaka et al. (Electrochim. Acta. 146, 2014). The GDL through-plane distributions and volumes of liquid water measured by two techniques are in excellent agreement. From this work, synchrotron X-ray radiography is shown to be a powerful technique that is both precise and accurate for measuring the spatial distribution of liquid water in miniature operating PEM fuel cells.